Implementation of Policies on The Selection, Appointment and Dismissal of Kuwu in The Community and Village Empowerment Office of Cirebon Regency - Rexy Nakula Urbaningrum (Journal Of Social Science (JoSS), 2025)
The research that the writer did was about "Implementation of policy about election, appointment and dismissal of village head in community office" (Case study in matangaji village district source Cirebon regency). Based on observations made by researchers in the district of Cirebon about 18 village heads of the village is low-educated only a diploma package C. Researchers take samples in the village matangaji Sumber-Cirebon. Why teke a sample in the village matangaji Sumber-Cirebon due to the village that has the village head certified C- Package. Village has decreased and incremented their performance and performance. The above conditions are based on the research assumptions are that one of them is because the village head is poorly educated and leads to a lack of performance evaluation from the village head himself. Let alone the education we receive is very influential to provide direction and good examples to the employees. The research method used by the writer is using qualiltive method. The author uses Edwards III theory with dimensions: Communication, resources, disposition and bureaucratic structure. The results of research indicate that the implementation of government policy number 60 year 2017 is misused in its implementation, because not the higher education is preferred but important the original villagers in order to become the village head, yet for the present high education and experience that deserve to be the head of the village because it will improve the achievement of the village.